Early conversion of pediatric kidney transplant patients to everolimus with reduced tacrolimus and steroid elimination: Results of a randomized trial. Issue 3 (18th October 2018) - Tönshoff, Burkhard; Ettenger, Robert; Dello Strologo, Luca; Marks, Stephen D.; Pape, Lars; Tedesco‐Silva, Helio; Bjerre, Anna; Christian, Martin; Meier, Matthias; Martzloff, El‐Djouher; Rauer, Barbara; Ng, Jennifer; et al.
Abstract : In a 12‐month, multicenter, open‐label study, 106 children were randomized at 4 to 6 weeks after kidney transplantation to switch to everolimus with reduced TAC (EVR/rTAC) and steroid elimination from month 5 posttransplant or to continue standard tacrolimus with mycophenolate mofetil (sTAC/MMF) and steroids. The cumulative incidence of a co‐primary efficacy end point (biopsy‐proven acute rejection [BPAR], graft loss, or death from randomization to month 12) was 10.3% with EVR/rTAC and 5.8% with sTAC/MMF (difference 4.4%; P = .417). BPAR occurred in 9.6% and 5.6% of patients, respectively. Patient and renal allograft survival were 100%. The co‐primary end point of mean estimated glomerular filtration rate at month 12 was 76.2 mL/min/1.73 m 2 with EVR/rTAC and 72.5 mL/min/1.73 m 2 for sTAC/MMF (difference 3.8 mL/min/1.73m 2 ; P = .49). One EVR/rTAC patient developed posttransplant lymphoproliferative disease. Longitudinal growth and sexual maturation were equivalent between groups. The randomized drug regimen was discontinued in 34.6% and 13% of patients in the EVR/rTAC and sTAC/MMF groups, respectively ( P = .024), and discontinued due to adverse events/infections in 25.0% and 11.1% of patients ( P = .062). In conclusion, early conversion of pediatric kidney transplant patients from TAC, MMF, and steroids to EVR/rTAC and steroid withdrawal maintains immunosuppressive efficacy and preserves renal function. Abstract : This multicenter randomized controlled trial in pediatric renal transplant recipients finds that early conversion from standard‐dose tacrolimus, mycophenolate mofetil, and steroids to everolimus, reduced‐dose tacrolimus, and steroid withdrawal maintains immunosuppressive efficacy and preserves renal function.